Optimizing Beef Fattening Management Strategies in Sadar Upazila, Kushtia: A Comprehensive Study - Mamun, Mustakim; Islam, Khairul; Kharbuja, Alpha; Rahman, Md Zillur; Bhuiyan, Md Ismile Hossain; Nirob, Ahmed Istiaque; Sikder, Tahmina; Ali, Mahabbat (Research in Agriculture Livestock and Fisheries, 2025)
Beef cattle are crucial for Bangladesh's economy, providing essential animal protein. However, beef cattle farmers in Kushtia Sadar Upazila, Kushtia District, face challenges like limited marketing channels, vaccination awareness, and disease outbreaks. A study interviewed 60 respondents, including 43.33% women and 24% young individuals, to examine the situation. Among the respondents, 36.67% raised cattle exclusively for Qurbani haat purposes, while 63.33% raised cattle for mixed purposes. Most farmers (73.33%) owned up to four cattle, with some managing larger herds. Indigenous cattle accounted for 36.63% of respondents, while crossbreed cattle made up 63.37%. The majority of farmers used typical feed ingredients for cattle's ration. Around 54% employed vitamin-mineral premix, while 46% did not. Disease prevalence indicated that nearly 70% of farms remained disease-free, but 20% encountered health issues like diarrhea and bloat. Lumpy skin disease affected almost 7% of farms, and foot and mouth disease affected 3%. When seeking medical support, 73.33% relied on village quacks, while 26.67% sought assistance from the Upazila veterinary hospital. Approximately 47% of respondents had connections with middlemen for marketing. The study revealed inadequate biosecurity practices on almost 40% of farms. To address the primitive management practices in beef cattle fattening and enhance production, the study highlighted the need for motivation and extension services. These measures can improve marketing, vaccination awareness, and disease prevention among beef cattle farmers in the region. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 175-186